"We are not in Geneva on the Human Rights Council": Indigenous peoples' experiences with the World Heritage Convention. Issue 4 (November 2022) - Disko, Stefan; Sambo Dorough, Dalee
Abstract: This article examines Indigenous peoples' experiences with the United Nations Educational, Scientific and Cultural Organization's (UNESCO) World Heritage Convention against the backdrop of their rights as recognized in the 2007 United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) and reviews the efforts of Indigenous peoples and human rights mechanisms to ensure respect for Indigenous peoples' rights, cultures, and values in World Heritage sites. Although the Convention's governing bodies have adopted policy and operational guidelines "encouraging" states parties to respect Indigenous peoples' rights, many nomination, management, and protection processes of World Heritage sites continue to be marked by an exclusion of Indigenous peoples from decision making, a lack of respect for their relationship to the land, and disregard for their traditional livelihoods and cultural heritage. Human rights violations against Indigenous peoples continue to occur unabated in many sites and are in many ways enabled, and sometimes even driven, by decision making under the Convention. This article argues that there is an unacceptable disconnect between this Convention and the UN human rights system, with significant implications for the Convention's and UNESCO's credibility, and that a concerted effort should be made to align this UN Convention with the UNDRIP and the human rights purposes of the UN Charter and the UNESCO Constitution.